Understanding the edge crack phenomenon in ceramic laminates - O. Ševe?ek,; M. Kotoul; D. Leguillon; E. Martin; R. Bermejo (Fracture and Structural Integrity)
Layered ceramic materials (also referred to as “ceramic laminates”) are becoming one of the most promising areas of materials technology aiming to improve the brittle behavior of bulk ceramics. The utilization of tailored compressive residual stresses acting as physical barriers to crack propagation has already succeeded in many ceramic systems. Relatively thick compressive layers located below the surface have proven very effective to enhance the fracture resistance and provide a minimum strength for the material. However, internal compressive stresses result in out-of plane stresses at the free surfaces, what can cause cracking of the compressive layer, forming the so-called edge cracks. Experimental observations have shown that edge cracking may be associated with the magnitude of the compressive stresses and with the thickness of the compressive layer. However, an understanding of the parameters related to the onset and extension of such edge cracks in the compressive layers is still lacking. In this work, a 2D parametric finite element model has been developed to predict the onset and propagation of an edge crack in ceramic laminates using a coupled stress-energy criterion. This approach states that a crack is originated when both stress and energy criteria are fulfilled simultaneously. Several designs with different residual stresses and a given thickness in the compressive layers have been computed. The results predict the existence of a lower bound, below no edge crack will be observed, and an upper bound, beyond which the onset of an edge crack would lead to the complete fracture of the layer.